Catalyst-Free One-Pot Synthesis of Chromeno-Imidazo-Pyridinones by an Aza-Michael Addition/Rearrangement/Heterocyclization Tandem Reaction - Lakhdari, Houria; Talhi, Oualid; Hassaine, Ridha; Taibi, Nadia; Mendes, Ricardo F.; Almeida Paz, Filipe A.; Bennamane, Norah; Nedjar-Kolli, Bellara; Bachari, Khaldoun; Silva, Artur M. S. (Synlett, 2018)
A one-pot synthesis of a novel series of chromeno-imidazo-pyridinone derivatives from 3-[(2-hydroxyphenyl)-3-oxoprop-1-en-1-yl]chromones and ethane-1,2-diamine at room temperature under catalyst-free conditions has been successfully developed. This approach involves a tandem aza-Michael addition reaction, a chromone-to-chromanone rearrangement, and a heterocyclization sequence, leading to chromeno-imidazo-pyridinone polyheterocycles. The structure and absolute configurations of the new compounds were elucidated by a combination of 1D- and 2D-NMR analyses and single-crystal X-ray diffraction.
Keywords: chromones; ethanediamine; chromeno-imidazo-pyridinones; one-pot synthesis; tandem reaction; aza-Michael addition